1988
DOI: 10.1111/j.1600-0714.1988.tb01536.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) DNA sequences in oral precancerous lesions and squamous cell carcinoma demonstrated by in situ hybridization

Abstract: A series of routinely processed, paraffin‐embedded biopsies from 73 surgically treated oral precancerous lesions (OPL) (22 cases), and oral squamous cell carcinomas (SCC) (51 cases), was first screened using an in situ DNA hybridization technique with a human papillomavirus (HPV) DNA probe cocktail containing the 35S‐labelled DNA of HPV types 6, 11, 13, 16, 18 and 30. The specific HPV types in lesions shown to contain HPV DNA in this procedure were further analysed by using in situ hybridization and the 6 HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
1
6

Year Published

1991
1991
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 26 publications
4
45
1
6
Order By: Relevance
“…In another series, HPV 6, 11, 16 and 18 DNA were found in 6/51 oral SCCs and in 6/21 oral precancer lesions (22). Loning et al (23) confirmed this report, detecting HPV 11 and 16 DNA in 3/6 oral carcinomas.…”
Section: Discussionsupporting
confidence: 74%
“…In another series, HPV 6, 11, 16 and 18 DNA were found in 6/51 oral SCCs and in 6/21 oral precancer lesions (22). Loning et al (23) confirmed this report, detecting HPV 11 and 16 DNA in 3/6 oral carcinomas.…”
Section: Discussionsupporting
confidence: 74%
“…Oral cancer biopsies have also been shown, in some cases, to contain HPV sequences, de Villiers et al (1985) and Adler-Storthz et al (1986b) detected HPV-2 DNA in oral squamous and verrucous carcinomas, and DNAs of HPV-16 (de Villiers et al, 1985;Maitland et al, 1987) and HPV-18 (Syrjanen et al, 1988) have been reported in other oral squamous celt carcinomas. Additionally, Maitland et al (1987Maitland et al ( , 1989 found that a large proportion of normal oral mucosal samples, as well as carcinomas, exclusively contain HPV-16 sequences, which in most cases varied from the prototype virus in their PstI restriction pattern.…”
mentioning
confidence: 99%
“…p53 expression was inversely cor- infections in uterine cervical lesions, their prevalence in oral lesions is highly variable, e.g. 0-78% for oral SCC [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . This variability may stem from differences in the methods used to detect HPV-DNA such as PCR, Southern blot hybridization and in situ hybridization (ISH).…”
Section: Introductionmentioning
confidence: 99%